Asean human rights body: possible terms of reference / Noor Yasmin Samsudin, Nur Azizah Jaafar - Samsudin, Noor Yasmin; Jaafar, Nur Azizah (2008)
Human rights are the basic rights and freedoms to which all humans are entitled, often held to include civil and political rights, such as the right to life and liberty, freedom of expression, and equality before the law; and social, cultural and economic rights, including the right to participate in culture, the right to food, the right to work, and the right to education. As stated in Article 1 of the United Nations Universal Declaration of Human Rights (UDHR), "All human beings are born free and equal in dignity and rights. They are endowed with reason and conscience and should act towards one another in a spirit of brotherhood." The enforcement of international human rights law is the responsibility of the Nation State, and it's the primary responsibility of the State to make human rights a reality. Although Article 14 of ASEAN Charter provides the establishment of human rights body in conformity with its (Association of Southeast Asian Nation) purpose, nevertheless, no terms of reference for such body has been determined yet. Thus, it can be said that the human rights body created under the Charter is dysfunctional to play its role in upholding human rights in Southeast Asia. Thus, this research project is carried out to highlight the violation of some major human rights in ASEAN Member States. Besides underlining the issues, this research project also completed an analysis of the European Convention on Human Rights and the Protocol to the African Charter on Human and Peoples' Rights on the Establishment of an African Court on Human and Peoples' Rights before any recommendations of the possible terms of reference for the ASEAN human rights body can be made. Upon emphasizing on the human rights and the analysis, some recommendations on the possible terms of reference that may be adopted by the ASEAN human rights court body are made.